In vivo evidence of interaction between interferon-stimulated gene factors and the interferon-stimulated response element. - Pine, R (1989)
Constitutive and interferon-inducible DNase hypersensitive sites in vivo are located in interferon-stimulated gene promoters near sequences that specifically bind constitutive or interferon-inducible proteins in vitro. Induced sites and proteins are transient or maintained, depending on cell type. Interferon-stimulated gene transcription is transient or maintained in parallel.